Enhancement of violaxanthin accumulation in Nannochloropsis oceanica by overexpressing a carotenoid isomerase gene from Phaeodactylum tricornutum - Sun, Yan; Xin, Yi; Zhang, Luyao; Wang, Ying; Liu, Ruolan; Li, Xiaohui; Zhou, Chengxu; Zhang, Lin; Han, Jichang (Frontiers in Microbiology, 2022)
Nannochloropsis has been considered as a promising feedstock for the industrial production of violaxanthin. As a key premise for the violaxanthin production from Nannochloropsis, rational breeding strategy via genetic engineering is still vacant. All-trans-lycopene locates in the first branch point of carotenogenesis. The carotenoid isomerase (CRTISO), catalyzing the lycopene formation, is thus regarded as a key enzyme for carotenogenesis. Phaeodactylum tricornutum can accumulate high-level carotenoids under optimal conditions. Therefore, it is feasible to improve violaxanthin level in Nannochloropsis by overexpression of PtCRTISO. Protein targeting analysis of seven PtCRTISO candidates (PtCRTISO1–6 and PtCRTISO-like) demonstrated that PtCRTISO4 was most likely the carotenoid isomerase of P. tricornutum. Moreover, the transcriptional pattern of PtCRTISO4 at different cultivation periods was quite similar to other known carotenogenesis genes. Thus, PtCRTISO4 was transformed into N. oceanica. Compared to the wild type (WT), all three transgenic lines (T1–T3) of N. oceanica exhibited higher levels of total carotenoid and violaxanthin. Notably, T3 exhibits the peak violaxanthin content of 4.48 mg g-1 dry cell weight (DCW), which is 1.68-folds higher than WT. Interestingly, qRT-PCR results demonstrated that phytoene synthase (NoPSY) rather than ζ-carotene desaturase (NoZDS) and lycopene β-cyclase (NoLCYB) exhibited the highest upregulation, suggesting that PtCRTISO4 played an additional regulatory role in terms of carotenoid accumulation. Moreover, PtCRTISO4 overexpression increased C18:1n-9 but decreased C16:1n-7, implying that C18:1 may serve as a main feedstock for xanthophyll esterification in Nannochloropsis. Our results will provide valuable information for the violaxanthin production from Nannochloropsis.